Firstline a direct aspiration first pass technique versus firstline stent retriever for acute basilar artery occlusion: a systematic review and meta-analysis. (28th January 2019) - Ye, Gengfan; Lu, Jun; Qi, Peng; Yin, Xiaoliang; Wang, Lijun; Wang, Daming
Abstract : Introduction: Acute basilar artery occlusion (BAO) can result in extremely high disability and mortality. Stent retrievers (SRs) can achieve a high recanalization rate for BAO, therefore improving favorable outcomes. However, the efficacy of a direct aspiration first pass technique (ADAPT) to treat BAO is unclear. Our aim was to compare the efficacy and safety of firstline ADAPT with that of firstline SR for patients with acute BAO. Methods: Three databases were systematically searched for literature reporting outcomes on thrombectomy for acute BAO with both firstline ADAPT and firstline SR. The modified Newcastle–Ottawa scale was applied to assess bias risk. The random effects model was used. Results: Of 50 articles, 5 cohort studies (2 prospective and 3 retrospective) were included in our research. 193 cases were treated with firstline ADAPT and 283 cases received firstline SR. Successful recanalization rate was significantly higher in the firstline ADAPT group (OR=2.0, 95% CI 1.1 to 3.5). Procedure time (mean difference=−27.6 min, 95% CI −51.0 to −4.3) and the incidence of new territory embolic event (OR=0.2, 95% CI 0.05 to 0.83) was significantly less in the firstline ADAPT group. No significant difference was observed between the firstline ADAPT and firstline SR groups for rate of complete recanalization, rescue therapy, any hemorrhagic complication, favorable outcomes, or mortality at 90 days. Conclusions: Our meta-analysis suggested that for patients with acute BAO, firstline ADAPT might achieve higher and faster recanalization, comparable neurological improvement and safety compared with firstline SR. Further studies are needed to confirm these results.